Intra‐arterial methylene blue injection into ex vivo colorectal cancer specimens improves lymph node staging accuracy: a randomized controlled trial. (September 2014) - Borowski, D. W.; Banky, B.; Banerjee, A. K.; Agarwal, A. K.; Tabaqchali, M. A.; Garg, D. K.; Hobday, C.; Hegab, M.; Gill, T. S.
Abstract Aim A randomized controlled trial was carried out to study the effect of a recently proposed technique of ex vivo intra‐arterial methylene blue injection of the surgical specimen removed for colorectal cancer on lymph node harvest and staging. Method Between May 2012 and February 2013, 100 consecutive colorectal cancer resection specimens in a single institution were randomly assigned to intervention (methylene blue injection) and control (standard manual palpation technique) groups before formalin fixation. The specimen was then examined by the histopathologist for lymph nodes. Results Both groups were similar for age, sex, site of tumour, operation and tumour stage. In the intervention group, a higher number of nodes was found [median 23 (5–92) vs 15 (5–37), P < 0.001], with only one specimen not achieving the recommended minimum standard of 12 nodes [1/50 (2%) vs 8/50 (16%), P = 0.014]. However, there was no upstaging effect in the intervention group [23/50 (46.0%) vs 20/50 (40.0%); P = 0.686]. With a significantly lower number of nodes harvested in rectal cancer, the positive effect of the intervention was particularly observed in the patients who underwent preoperative neoadjuvant radiotherapy [median 30 nodes (12–57) vs 11 (7–15); P = 0.011; proportion of cases with < 12 nodes 0/5 vs 5/8 (62.5%), P = 0.024]. Conclusion Ex vivo intra‐arterial methylene blue injection increases lymph node yield and can help to reduce the number of cases with a lower‐than‐recommended number of nodes, particularly in patients with rectal cancer having neoadjuvant treatment. The technique is easy to perform, cheap and saves time.